Innovation through urban diversity and achieving comprehensive sustainable urbanism from a community-oriented approach - Cheshmehzangi, Ali; Aurelia Li, Hei Men (2020)
In current urban studies focused on pathways of sustainable urbanism, the main discourse is on the development of all-inclusive approaches or comprehensive methods that could encompass multiple factors of sustainability. As a result, a bigger emphasis has been given to other dimensions of “cultural” or “governance” (also known as institutional). In more recent years, more scholarly research studies refer to governance as the fourth pillar of sustainability, and more research studies analyse the multi-dimensional methods of socio-cultural, socio-economic, etc. These factors all have major impacts on the social, environmental, and economic aspects of the city. As a result, this research study aims to test the notion of “sustainable urbanism” from a behavioural perspective, which includes market development behavior and political economy (or mixed economy). This study promotes urban diversity from the multiplicity of diversity across the physical environment, social and economic systems, cultural attributes, people backgrounds, professions and sectors, etc. This then leads to discussions on innovation through urban diversity. Hence, it is important to evaluate how diversity promotes sustainable urbanism through specific economic and social systems in contemporary city development scenarios. The findings from this study feed into matters of urban diversity and urban innovation, and towards pathways of sustainable urbanism.